Damage to sheet blades of small-leaved lime of larvae of the lime leaf miner in the green stands of the Central Botanical Garden National Academy of Sciences of Belarus in 2015–2019 - Sinchuk, Aleh V.; Buga, Sergey V. (Journal of the Belarusian State University. Ecology, 2020)
Studies on damage of small-leaved lime (Tilia cordata Mill., 1768; Malvaceae) by invasive alien species, lime leaf miner (Phyllonorycter issikii (Kumata, 1963); Lepidoptera: Gracillariidae: Lithocolletinae), were carried out in the Central Botanical Gardens of the National Academy of Sciences of Belarus in Minsk throughout 2015–2019. During the periodafter the end of development of the first generation larvae, in the lower part of crowns less than 15% of leaf blades were inhabited, but after the end of development of the second generation larvae more than 51 % of ones were colonized by the miner. The values of the parameter in some cases varied significantly. The number of individual mines of Ph. issikii onleaf blades of T. cordata during the period after completion of development of larvae of the first generation varied from 1 to 6 per leaf, after completion of development of larvae of the second generation – from 1 to 19 per leaf, statistically significant (p
Keywords: Phyllonorycter issikii; invasive species; decorative green stands; leaf mine square; colonization of leaf blades